Ghrelin mediates stress-induced food-reward behavior in mice - Chuang, Jen-Chieh; Perello, Mario; Sakata, Ichiro; Osborne-Lawrence, Sherri; Savitt, Joseph M.; Lutter, Michael; Zigman, Jeffrey M. (The Journal of Clinical Investigation, 2011)
The popular media and personal anecdotes are rich with examples of stress-induced eating of calorically dense “comfort foods.” Such behavioral reactions likely contribute to the increased prevalence of obesity in humans experiencing chronic stress or atypical depression. However, the molecular substrates and neurocircuits controlling the complex behaviors responsible for stress-based eating remain mostly unknown, and few animal models have been described for probing the mechanisms orchestrating this response. Here, we describe a system in which food-reward behavior, assessed using a conditioned place preference (CPP) task, is monitored in mice after exposure to chronic social defeat stress (CSDS), a model of prolonged psychosocial stress, featuring aspects of major depression and posttraumatic stress disorder. Under this regime, CSDS increased both CPP for and intake of high-fat diet, and stress-induced food-reward behavior was dependent on signaling by the peptide hormone ghrelin. Also, signaling specifically in catecholaminergic neurons mediated not only ghrelin’s orexigenic, antidepressant-like, and food-reward behavioral effects, but also was sufficient to mediate stress-induced food-reward behavior. Thus, this mouse model has allowed us to ascribe a role for ghrelin-engaged catecholaminergic neurons in stress-induced eating.